The Effect of Maternal Labor Supply on Children: Evidence from Bunching - Caetano, Carolina; Caetano, Gregorio; Nielsen, Eric; Sanfelice, Viviane (Journal of Labor Economics, 2025)
We study the eﬀect of maternal labor supply in the ﬁrst three years of life on early childhood cognitive skills. We pay particular attention to heterogeneous eﬀects by the skill of the mother, by the intensity of her labor supply, and by her pre-birth wages. We correct for selection using a control function approach which uses the fact that many mothers are bunched at zero working hours – skill variation in the children of these bunched mothers is informative about the eﬀect of unobservables on skills. We ﬁnd that maternal labor supply typically has a signiﬁcant, negative eﬀect on children’s early cognitive skills, with more negative eﬀects for higher-skill mothers. By contrast, we do not ﬁnd signiﬁcant heterogeneity depending on the pre-birth wage rate of the mother. These ﬁndings suggest that there may be more scope to avoid short-term, unintended consequences of maternal labor supply through policies that promote more ﬂexible work arrangements rather than through policies that increase the ﬁnancial rewards to working.